1999
DOI: 10.1111/j.1741-6612.1999.tb00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Falls in the Elderly Rehabilitation Client

Abstract: Objective: The purpose of the study was to determine risk factors associated with falls in an elderly rehabilitation client group.Method: The study involved retrospective analysis of incident reports/medical files over four years of 87 clients who had fallen in the aged care rehabilitation unit under study. A comparison group was chosen of 87 randomly selected clients who did not fall during their rehabilitation program. Factors involved were analysed using a logistic regression equation to develop a model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…After full text screening, eight articles concerning six studies met our inclusion criteria. [17][18][19][20][21][22][23][24] Most of the studies excluded during full-text screening, were excluded either because the studies were not conducted in a rehabilitation setting or because patients were not exclusively 65 years of age or older. The median year of publication was 2005 (range: 1999 to 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After full text screening, eight articles concerning six studies met our inclusion criteria. [17][18][19][20][21][22][23][24] Most of the studies excluded during full-text screening, were excluded either because the studies were not conducted in a rehabilitation setting or because patients were not exclusively 65 years of age or older. The median year of publication was 2005 (range: 1999 to 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The average age of the patients ranged from 77 to 83 years, the percentage of women ranged from 56% to 81%, and the percentage of fallers ranged from 15% to 54%. All included studies were longitudinal; two were case-control studies, 17,18 two were RCTs 19,20 and four were prospective cohort studies. [21][22][23][24] All studies presented potential biases ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Research has identified lower limb weakness from various aetiologies as a major intrinsic contributor (Janken et al, 1986;Morse et al, 1987;Byers et al, 1990;Salgado et al, 1994). Abnormalities of gait and balance (Tinetti et al, 1986;Barclay, 1988;Stalenhoef et al, 1997;Stevenson et al, 1998), neurological pathologies such as Parkinson's Disease (Dolinas et al, 1997;Ashburn et al, 2001), primary diagnosis of stroke and amputation (Barr, 1999) have been implicated. Visual contrast sensitivity, proprioception in the lower limbs, quadriceps strength, reaction time and sway on a foam rubber surface with the eyes open significantly discriminated multiple falls from a single fall or no falls (Lord et al, 1994).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous fall history in the over-60s age group has been identified as a discrete risk factor (Nevitt et al, 1989;Gluck et al, 1996). Altered mental status, often cited as cognitive impairment caused by confusion or disorientation, is a commonly reported risk factor (Mion et al, 1989;Salgado et al, 1994;Stalenhoef et al, 1997;Hakim, 1998;Barr et al, 1999). The literature reports many medications that can increase the likelihood of falling.…”
Section: Literature Reviewmentioning
confidence: 99%
“…10 Impaired balance, strength and mobility have frequently been reported as significant risk factors for falls. [11][12][13][14][15][16][17][18] Previous literature reviews have concluded that a variety of exercise programme models may be beneficial for improving balance, strength and mobility amongst frail and older patient groups. [19][20][21] Exercise interventions such as group tai chi, group resistance training and home-based strength, balance and mobility programmes have also been shown to reduce falls amongst community-dwelling older adults both in isolation, 22,23 and in combination with other interventions such as education programmes, 24 management of reduced vision 25 and home hazard modification.…”
Section: Introductionmentioning
confidence: 99%